Discrimination in Consumer Lending - Elliehausen, Gregory E.; Lawrence, Edward C. (The Review of Economics and Statistics, 1990)
This paper tests for the existence of discrimination in consumer lending by finance companies in Texas before the passage of the Equal Credit Opportunity Act. The data used permit conclusions about discrimination in the market, not just in the behavior of a small number of creditors. The tests suggest that lenders did not discriminate against factors now protected by ECOA. These companies may have discriminated against single borrowers of both sexes and against widows but not married women or divorced borrowers. The results support the view that consumer credit markets as a whole were not characterized by widespread systematic discrimination. Copyright 1990 by MIT Press.